A constitutive analysis of the extensional flows of nearly monodisperse polyisoprene melts. (8th November 2016) - Rasmussen, Henrik Koblitz
Abstract: Here two particular formulations [M.H. Wagner, S. Kheirandish, O. Hassager, Journal of Rheology 49 (6) (2005) 1317–1327; H.K. Rasmussen, Q. Huang, Rheologica Acta 53 (3) (2014) 199–208; G. Marrucci, G. Ianniruberto, Macromolecules 37 (10) (2004) 3934–3942] of the 'interchain pressure' [39], incorporated into the molecular stress function method [M.H. Wagner, S. Kheirandish, O. Hassager, Journal of Rheology 49 (6) (2005) 1317–1327], are used to assess the extensional [J.K. Nielsen, O. Hassager, H.K Rasmussen, G.H. McKinley, Journal of Rheology 53 (6) (2009) 1327–1346; G. Liu, H. Sun, S. Rangou, K. Ntetsikas, A. Avgeropoulos, S.-Q. Wang, Journal of Rheology 57 (1) (2013) 89–104] and shear viscosities [D. Auhl, J. Ramirez, A.E. Likhtman, P. Chambon, C. Fernyhough, Journal of Rheology 52 (3) (2008) 801–835] of narrow molecular weight distributed (NMMD) polyisoprene melts. These two formulations are expected to represent the highest [M.H. Wagner, S. Kheirandish, O. Hassager, Journal of Rheology 49 (6) (2005) 1317–1327, G. Marrucci, G. Ianniruberto, Macromolecules 37 (10) (2004) 3934–3942] and lowest level [H.K. Rasmussen, Q. Huang, Rheologica Acta 53 (3) (2014) 199–208] of the 'interchain pressure'. The needed Rouse times are here defined as τ R / τ max ∝ ( M / M e ) −1.4 with a proportional factor of 1.4, achieved based on the viscosity measurement. τ max is the maximal relaxation time, M the molecular weight and the entanglement molecular weight M e = ( 4 / 5 ) ρRT / G N 0 [M. Doi M, S.F. Edwards, The Theory of Polymer Dynamics; Clarendon Press: Oxford (1986)]. ρ is the density, R the gas constant, T the temperature and G N 0 the plateau modulus. The method by [M.H. Wagner, S. Kheirandish, O. Hassager, Journal of Rheology 49 (6) (2005) 1317–1327, G. Marrucci, G. Ianniruberto, Macromolecules 37 (10) (2004) 3934–3942] predicts start-up of extensional viscosities significantly below the measured value. The formulations by [H.K. Rasmussen, Q. Huang, Rheologica Acta 53 (3) (2014) 199–208] seem to be in agreement with both the start-up of extension as well as the shear flow of all NMMD polyisoprenes. Potential non-isothermal effects were addressed computationally using the pseudo time principle, assuming the most critical case of adiabatic heating. Graphical abstract: Highlights: The constant interchain pressure idea predicts the flow of monodisperse polyisoprenes. Agreement with startup of extension viscosity of nearly monodisperse polyisoprenes. Agreement with startup and steady shear viscosity of nearly monodisperse polyisoprene.